Skin diseases in elite athletes - Liebich, C.; Wegin, V. V.; Marquart, C.; Schubert, I.; von Bruehl, M.-L.; Halle, M.; Oberhoffer, R.; Wolfarth, B. (International Journal of Sports Medicine, 2021)
An athlete`s skin has to cope with various stressors that influence skin integrity. This study investigated the effect of intense sporting activity at a competitive level on skin health, independent of the type of sport. The prevalence of dermatoses in elite athletes who exercise 8 or more hours per week was compared to recreational athletes. By applying a questionnaire, we acquired data from n=492 recruited athletes and recreational athletes regarding the prevalence of dermatoses, the extent of physical activity, and sports discipline practiced. Compared to the reference group, elite athletes showed less inflammatory, traumatic, infectious, and sebaceous skin diseases and especially neurodermitis, pruritus, bullae, tinea pedis, acne, and herpes were less common. Women suffered from skin diseases more often than men. With advanced age, the incidence of dermatoses increased, but less so among elite athletes. The discipline practiced and the duration of training, especially when performed outdoors, strongly influenced the development of dermatoses. Even though the skin of athletes is exposed to higher stress levels and physical strain, we can state that intensive physical activity seems to act as a protecting factor against skin diseases and significantly promotes skin health.